KESESUAIAN PENYIMPANAN PERBEKALAN FARMASI DI GUDANG INSTALASI FARMASI RUMAH SAKIT ISLAM BANJARMASIN - Amaliyah Wahyuni; Raihana Raihana; Amalia Amalia (Jurnal Insan Farmasi Indonesia, 2022)
Storage of supplies of one of the components of supplies in the hospital. Storage of supplies such as medicines, medical devices and consumable medical materials in the Hospital Pharmacy Installation Warehouse (IFRS) should be highly considered because not all medicines, medical devices and consumable medical materials are treated equally in their storage, ensuring properly maintained. Improper pharmaceutical supplies can result in rapid damage and expiry. The purpose of this study is to determine the percentage of suitability of pharmaceutical supply storage in the Pharmacy Installation Warehouse of Banjarmasin Islam Hospital. Non-experimental research is observation using observation sheet based on the suitability of Permenkes No.72 Year 2016 and SPO RS Islam. The population is Islam IFRS Warehouse and the sample is Islam Hospital Pharmacy Installation Warehouse using saturated sampling method. The result of the percentage of suitability of pharmaceutical supplies storage in the Pharmacy Installation Warehouse of The Islam Hospital Banjarmasin. The results of the conformity permenkes No. 72 Year 2016; pharmaceutical preparations 309 indicators (71.52%); MD 136 indicators (62.96%); and CM 133 indicators (61.57%). Conformity Results Based on SOP Islam Banjarmasin Hospital Year 2018 namely; Pharmaceutical Preparations 244 indicators (72.62%);, and MD 167 indicators (69.58%) and CMM 166 indicators (69.16%).